Implementation of the Merdeka Curriculum at RA 02 Darul Ulum Batu - Nurhayati, Farihah; Faujiyah, Siti; Samawi, Ahmad; Dian, Yudithia (DZURRIYAT : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This research explores the practical and theoretical implications of implementing the Independent Curriculum (Kurikulum Merdeka) at RA 02 Darul Ulum, an Islamic-based early childhood education institution, with a focus on integrating religious values and holistic skill development. Using a qualitative approach through a case study at RA Al-Mukarromah, data were collected from teacher interviews, learning observations, and curriculum document analysis. The results indicate that effective implementation enhances teacher flexibility, student engagement, and parent collaboration, while addressing challenges such as resource readiness. The scientific contribution of this research explicitly lies in developing an integrated curriculum model that combines constructivist theory with Islamic values, which has not been deeply explored in the context of Indonesian early childhood education (PAUD). The novelty lies in the emphasis on the spiritual dimension as a holistic element, addressing the literature gap that focuses more on academic aspects alone. The urgency of these findings is evident from the potential of the Independent Curriculum to shape a morally upright generation in the era of globalization. Practically, these findings provide guidance for RA teachers to design innovative project-based learning, enhancing educational effectiveness and students' readiness to face contemporary challenges. Theoretically, the results strengthen Vygotsky's and Gardner's theories with empirical evidence that curriculum flexibility can accelerate children's cognitive-social-spiritual development, thus contributing to the expansion of the theoretical framework for multicultural early childhood education. This research recommends developing similar models on a national scale.